Penang : the fourth Presidency of India, 1805-1830 : ships, men and mansions - Langdon, Marcus (Penang : Areca Books, 2013)
A little over two centuries ago, Penang became the fourth most important settlement - a presidency - of the British East India Company's Indian territories. The fateful decision changed Penang's future forever, reshaping it into a key player in the international trade network linking Europe with India and China. The first of a three-volume series, Penang: The Fourth Presidency of India presents an in-depth and compelling narrative of this fascinating period in history, focusing specifically on the role shipbuilding played, the leading political personalities, and two historic buildings that highlight the struggles, successes and failures of the early settlement. Illustrated with several never-before-seen paintings, engravings and maps, the volume and those to follow will be the authoritative reference for historians and general readers for generations to come. -- Publisher's blurb.
Includes bibliographical references and index.
Keywords: East India Company -- History -- 19th century; Pinang -- Pictorial works; Pinang -- History -- 19th century